The Formation of Rural’s Labor Migration in Rural-Coastal of Aceh, Indonesia: Do Land-Factor or Other Household Characteristics Matters - Hadi, Shaummil; Wahyuni, Sri (International Journal of Science and Society, 2024)
As in other Indonesian provinces, Aceh is also experiencing demographic changes due to migration patterns. However, the migration rate in Aceh is not much significant in number compared to other provinces in Indonesia. As shown in the findings of this study. In the post-conflict and post-tsunami period, migration patterns in Aceh more influenced by economic factors. Moreover, the agricultural sector that dominates the structure of the regional GDP of Aceh unfortunately tends to decline every year in percentage and not so promising for rural household income and prompted the agricultural labour force to move to the non-agricultural sector and induces rural-urban migration. The study aims to assess the effects of land factors (agriculture) on individual migration decisions in households in four coastal villages in Bireuen district of Aceh. The research approach is the theory of economic migration. The method of analysis used in this study is statistically-descriptive and multiple linear regression analysis, to assess whether land ownership has a significant impact on the labour’s migration behaviour. In the findings of study, we found the relationship of land factor to migration pattern are both induce the “cost of opportunity” and the “hinder factor”. While land ownership does not significantly affect the likelihood of migration, other factors do. These include age, household size, composition of the household labour force, and poverty levels. This study are expected to cover the gaps in the literature on the migration and rural development studies in both Aceh and Indonesia.